Social Welfare Management Guidelines of the Elders in Bang Nam Chued Subdistrict Administrative Organization, Lang Suan District, Chumphon Province - Nokkhum, Apirak; Iemnawa, Onrudee; Ngamdi, Prachuab; Jaiphet, Chast; Rungsee, Pawida (Legal State Journal, 2023)
This research article aims to study (1) the social welfare service model of the elderly, (2) the problems of social welfare of the elderly, and (3) the approaches of social welfare management of the elderly in Bang Nam Chued Subdistrict Administrative Organization, Lang Suan district, Chumphon province. This research is qualitative research. The sample group consisted of relevant officers and 24 elderly aged 60 years. The research tools were semi-structured interview. Findings are as follows: Bang Nam Chued Subdistrict Administrative Organization provided services in all 4 areas. In accordance with Tambon Council and Tambon Administrative Authority Act, B.E. 2562, (7th revised edition), Section 66 and Act Prescribing Plans and Procedures for Distribution to Local Administrative Organizations, B.E. 2542, Section 16 (6), (10) and (19). (1) Medical and Public Health: budgets is divide to support the elderly health care. Including having staff to provide services at home. (2) Education: Organize a school for the elderly to learn and do activities together. Including providing study visits outside the area. (3) Occupational: Local agencies come to teach skills. To take on extra occupations according to the age of the elderly. (4) Payment of living allowances: has implemented the payment of allowances to the elderly that have been allocated from the government budget. The problem is most of the elderly people cannot afford the time. Some of them are bedridden. Some are in employment, and some miss out the right for the allowance caused by the lack of an extensive survey. To suggest solution guidelines, create a network, conduct a survey to inform the right to receive a pension and public relations about upcoming events. Transportation is also arranged for the elderly to travel to a service area. In addition, the elderly need help in Agriculture and Nutrition. Finally, they need public health officials to advise on caring for the bedridden elderly.